2010
DOI: 10.1063/1.3298846
|View full text |Cite
|
Sign up to set email alerts
|

Studies of emittance of multiply charged ions extracted from high temperature superconducting electron cyclotron resonance ion source, PKDELIS

Abstract: For the high current injector project at Inter University Accelerator Centre, a high temperature superconducting electron cyclotron resonance (ECR) ion source, PKDELIS, would provide the high charge state ions. The emittance of the ECR ion source is an important parameter to design further beam transport system and to match the acceptances of the downstream radio frequency quadrupole and drift tube linac accelerators of the high current injector. The emittance of the analyzed beam of PKDELIS ECR source has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
(7 reference statements)
0
2
0
Order By: Relevance
“…For the sake of completeness and usefulness of such plasma studies at higher rf power levels in large volume ECR sources, the instabilities have also been observed experimentally by the same Fourier analysis technique for a high temperature superconducting ECR ion source also known as PKDELIS [41,42] and it has been observed that there is a similar set of plasma instabilities. The source has an axial field of 1.8 T and 1.5 T at the injection and extraction side, respectively.…”
Section: Plasma Instabilities At Higher Rf Power and Confinement Fmentioning
confidence: 99%
“…For the sake of completeness and usefulness of such plasma studies at higher rf power levels in large volume ECR sources, the instabilities have also been observed experimentally by the same Fourier analysis technique for a high temperature superconducting ECR ion source also known as PKDELIS [41,42] and it has been observed that there is a similar set of plasma instabilities. The source has an axial field of 1.8 T and 1.5 T at the injection and extraction side, respectively.…”
Section: Plasma Instabilities At Higher Rf Power and Confinement Fmentioning
confidence: 99%
“…This is especially true for the heavier ions since their measured beam emittances are much lower. 3 Therefore, the total beam energy coming from the ion source is the product of the charge state and the sum of the extraction voltage and the plasma potential assuming a uniform potential difference between the plasma and the chamber wall. Since a significant energy spread can influence the longitudinal optics, it was felt necessary to measure the plasma potentials for various ions and its dependance on source tuning parameters.…”
Section: Introductionmentioning
confidence: 99%